2017
DOI: 10.1080/02668734.2017.1354908
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of radicalisation: a public health approach to understanding and intervention

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A considerable number of individuals appeared to be vulnerable in several ways. In fact, we found that 32.4% of CVE subjects had severe and complex problems to an extent that is comparable with homeless clients in Amsterdam (40). This finding is similar to a previous study by Fassaert et al (43) in a population of offenders of serious violent crime, of whom 35.9% had complex self-sufficiency problems to an extent that was comparable to homeless people in Amsterdam.…”
Section: 4supporting
confidence: 91%
See 2 more Smart Citations
“…A considerable number of individuals appeared to be vulnerable in several ways. In fact, we found that 32.4% of CVE subjects had severe and complex problems to an extent that is comparable with homeless clients in Amsterdam (40). This finding is similar to a previous study by Fassaert et al (43) in a population of offenders of serious violent crime, of whom 35.9% had complex self-sufficiency problems to an extent that was comparable to homeless people in Amsterdam.…”
Section: 4supporting
confidence: 91%
“…This information can be deducted by case or vignette studies and may be especially relevant in mental disorders like autism spectrum disorders, psychosis, PTSD and addictions ( 10 , 31 , 63 , 64 ). Further research is needed to shed more light on the role of mental disorder in the complex, individualized, heterogenous pathways to radicalization and terrorism ( 10 , 14 , 40 , 63 ). In the context of the screening for the CVE program, however, it is important to note that we actually do formulate individualized hypotheses on the association between the problem areas that are observed during the screening and the process of radicalization or violent behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR acts are the result of political, economic, social, and psychological processes that are often associated with increasing sympathy for violence seen as a legitimate mean to reach a specific (political) goal (Bhui & Jones, 2017; Bhui, Silva, Topciu, & Jones, 2016; Schmid, 2013). Although the relation between violent acting out and sympathy for VR is not linear, the latter may be considered as an early indicator of risk of involvement in extremist and violent activities later in life (Bhui et al, 2016).…”
Section: Future Orientation Depression and Sympathy For Vrmentioning
confidence: 99%
“…These ethical challenges include maintaining the confidentiality of people who access care and ensuring appropriate collaboration across the medical and criminal justice sectors. Cultural psychiatrists have advocated for public health approaches to the prevention of radicalization to violence (Bhui, et al, 2012;Bhui & Jones, 2017;Weine, et al, 2017). In this context, the term prevention covers a wide range of practices which include working at the whole population level on attitudes, grievances and social climate (primary prevention), as well as targeted interventions for individuals or groups that are deemed high risk (secondary prevention), and rehabilitation programs for those who have already been involved, to varying degrees, in extremist or radical activities leading to violence (tertiary prevention).…”
Section: Preventing Violent Radicalizationmentioning
confidence: 99%